Study on the mechanical characteristics of sand pebble surrounding rock considering the disturbance effect of tunnel excavation - Huang, Maozhou; Yu, Daidai; Li, Xin; Zhao, Yinting (Frontiers in Earth Science, 2024)
During tunnel construction in sand and pebble strata, soil disturbance is inevitable, leading to continuous changes in the soil properties. While indoor tests measure physical and mechanical parameters reflecting the soil properties in a specific state, they cannot depict the dynamic changes occurring during the construction process.Triaxial shear tests on sandy pebble soil under various perimeter pressures were conducted to enhance the accuracy of predicting deformation and strength characteristics amidst construction disturbance. A modified Duncan-Chang model was devised to capture the impact of disturbance on the strength-deformation characteristics of sandy pebble soils. This was achieved by establishing correlations between the modulus of elasticity, peak strength, and degree of disturbance. Furthermore, the modified model is utilized to derive the stress-strain relationship of sandy gravel soil under randomly disturbed conditions. Test results demonstrate the effectiveness of the modified Duncan-Chang model in illustrating the stress-strain relationship of sandy pebble soil under specified disturbed conditions.